The Relationship Between Smartphone Use, Social Support, and Mental Health in Collegiate Student-Athletes - Hohenstreiter, Trent Allan (East Carolina University)
Smartphones have become increasingly prevalent in today's society. Additionally, there has been a rise in mental health problems, particularly among collegiate student-athletes, where 21-33% report depressive symptoms and 28-40% report anxiety symptoms (Cox et al., 2017; Davoren & Hwang, 2014; Glascock & Poliakova, n.d.; H. Li et al., 2017). Previous research has linked elevated smartphone use to the presence of these mental health issues (Barry et al., 2022; Dobrean & Pasarelu, 2016), yet little is known about potential mediators in this relationship. Perceived social support emerges as a potential mediator, as collegiate student-athletes often rely on informal support during mental health challenges (Habeeb et al., 2022). Moreover, athletes who report having more social support from informal sources (i.e., teammates and friends) also report fewer depression and anxiety symptoms (Hagiwara et al., 2021). However, smartphones may hinder the creation of social support networks (Przybylski & Weinstein, 2013), potentially exacerbating mental health problems among collegiate student-athletes. PURPOSE: The purpose of this study was to gain a better understanding of the underlying factors of the mental health problems collegiate student-athletes experience by examining perceived social support as a mediator in the relationship between smartphone use and mental health problems. METHODS: A sample of 101 collegiate student-athletes (32 males and 69 females) completed a survey measuring demographic factors, smartphone use (i.e., total screen time, social media screen time, and social media use during daily activities), perceived social support (i.e., esteem, emotional, informational, and tangible), and mental health (i.e., depression symptoms, anxiety symptoms, and stress). RESULTS: Bivariate correlations revealed a significant association between total screen time and depressive symptoms (r = .24, p < .05), while perceived social support was inversely related to mental health problems (r = -.26, p < .01). However, there were no significant relationships observed between any variable of smartphone use and perceived social support, including its subscales (i.e., esteem, emotional, informational, and tangible support) and perceived social support did not mediate the relationship between smartphone use and mental health problems. CONCLUSION: In line with previous research, the present study suggests that collegiate student-athletes with greater smartphone use are more likely to experience depressive symptoms. Additionally, when they perceive higher levels of social support, they tend to experience fewer mental health problems, including depressive and anxiety symptoms. These findings provide valuable insights for collegiate student-athletes and their athletic support staff, highlighting the importance of educating them about the detrimental effects of smartphone use on mental health, specifically depressive symptoms, and the potential benefits of creating strong socials support circles to reduce mental health problems.
Keywords: Smartphone Use; Collegiate Student-Athletes; College athletes--Mental health; Sports--Psychological aspects; Smartphones--Health aspects; Social networks